New treatment strategies for bipolar disorder in the elderly - Kędziora-Kornatowska, Kornelia; Winiarek, Karolina; Murawska, Joanna; Guzowski, Cezary; Jabłońska, Monika; Błasik, Natalia; Wójcik, Agata; Lamch, Magdalena (Journal of Education, Health and Sport, 2022)
Introduction and objective: The purpose of this paper is to systematically review articles and new research in the context of bipolar geriatric patients. Materials and methods: PubMed searches were completed using the key terms bipolar disorder, bipolar elderly, bipolar depression, bipolar elderly treatment and review articles. In addition, references in these resources were searched. Search dates: 2010 to 2022. Description of the state of knowledge: Mental disorders in the context of the elderly concern all depressive disorders. A problem with other disorders such as bipolar disorder is also increasingly recognized. In the elderly, it is quite rare in the general cross-section of society, but it may have a higher percentage, e.g. in nursing homes and care institutions. This review article shows both the difference and the similarities in the course of this disease in older and younger patients. The most important and common aspect for both age groups is psychotherapy with parallel pharmacological treatment. The greatest difficulty in pharmacotherapy in the elderly is polypharmacy and numerous drug interactions, as well as different pharmacodynamics and pharmacokinetics of the drugs used compared to younger patients. Attention should also be paid to the differentiation of bipolar disorder from different types of dementia and other cognitive disorders. Therefore, one should strive to carefully assess the patient's need for a given treatment, establish appropriate periodic monitoring of treatment, and assess the risk of taking or not intervening. This article also aims to review new research and drugs that seem promising, while the individualized and interdisciplinary approach to a geriatric patient with BD is the most important finding of this review. Summary: Bipolar disorder in older people, compared to the younger population, should be treated pharmacologically in combination with psychotherapy. The elderly patient population requires a multidisciplinary approach due to the number of drugs used in a large number of diseases.